Should regulatory impact assessment have a role in Sweden's tranport planning? - Lena Nerhagen; Sara Forsstedt (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2019)
This paper describes the use of regulatory impact assessment (RIA) and cost-benefit analysis (CBA) for transport planning in Sweden and discusses the arguments for and against its use. The paper considers four main aspects: First, the Swedish planning context and existing requirements regarding the use of RIA. Second, the current focus of research regarding CBA for infrastructure investments in the Swedish transport sector and the need for greater focus on issues concerning regulation. Third, the difficulty to quantify and place monetary values on effects. Fourthly, the paper discusses the need to align incentives at all levels and across agencies.
Keywords: 330; Infrastrukturinvestition; Regulierung; Kosten-Nutzen-Analyse; Verkehrsplanung; Transportgewerbe; Schweden